2019
DOI: 10.1183/13993003.01959-2019
|View full text |Cite
|
Sign up to set email alerts
|

PET/CT features of extrapulmonary tuberculosis at first clinical presentation: a cross-sectional observational18F-FDG imaging study across six countries

Abstract: BackgroundA large proportion of the huge global burden of extrapulmonary tuberculosis (EPTB) cases are treated empirically without accurate definition of disease sites and extent of multi-organ disease involvement. Positron emission tomography (PET) imaging using 2-deoxy-2-(fluorine-18) fluoro-d-glucose (18F-FDG) in tuberculosis could be a useful imaging technique for localising disease sites and extent of disease.MethodsWe conducted a study of HIV-negative adult patients with a new clinical diagnosis of EPTB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 23 publications
2
17
0
Order By: Relevance
“…The sensitivity of [ 18 F]FDG-PET/CT at initial diagnosis in our study is comparable to those previously reported (97-100%) (8,9,(12)(13)(14). Additional unknown injured sites were discovered on PET1 in 52.7% of cases.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The sensitivity of [ 18 F]FDG-PET/CT at initial diagnosis in our study is comparable to those previously reported (97-100%) (8,9,(12)(13)(14). Additional unknown injured sites were discovered on PET1 in 52.7% of cases.…”
Section: Discussionsupporting
confidence: 89%
“…Such parameter is highly variable in the literature, from 10 to 69%, probably depending on the study population (disseminated or local tuberculosis). Discovered additional sites mainly concerned cutaneous lesions, liver lesions and abdominal lymph nodes not detected on CT. As compared to data of the literature (8,9,(12)(13)(14), the percentage of residual [ 18 F]FDG uptake in lesions at the end of antibiotherapy is higher in our study (82 vs. about 40-50% in most studies). This may be explained by the characteristics of the study population: only extra-pulmonary and mostly disseminated tuberculosis in our study when other studies included both pulmonary and other types of tuberculosis.…”
Section: Discussionsupporting
confidence: 48%
“…CT or PET Scans can identify more cases of extra-pulmonary TB and can detect cryptic changes which may not be visible on chest X-rays. However these imaging facilities are not available (PET) or not accessible for TB diagnosis in our country and many resoource poor regions (Bomanji et al, 2020a;Bomanji et al, 2020b). Our study found that alcohol users were two times more likely to have RPTB in univariate analysis (cOR 1.93, 95% CI (1.19 -3.15) p < 0.001) but was not significant in multivariate analysis.…”
Section: Discussionmentioning
confidence: 55%
“…18 F-FDG PET/CT, as a whole-body imaging method, has the advantage of localizing and monitoring the response to therapy in extrapulmonary TB when there is no pulmonary involvement and in identifying additional extrapulmonary sites of disease in TB. 18 F-FDG uptake can occur in sites such as the liver, abdominal lymph nodes, and bones (Figures 2 and 3), or diffusely in the spleen as a sign of active infection (Vorster et al, 2014;Rodriguez-Takeuchi et al, 2019;Bomanji et al, 2019). FDG PET/CT might also be useful to identify extrapulmonary involvement of the central nervous system, but MRI is considered superior in this setting (Vorster et al, 2014;Rodriguez-Takeuchi et al, 2019;Bomanji et al, 2019;Gupta et al, 2009;Chaudhary et al, 2017).…”
Section: Pet/ct In Active Tuberculosismentioning
confidence: 99%